ANALYSIS OF BENEFITS AND CHALLENGES TOWARDS MALAY TECHNOLOGICAL TERMINOLOGIES IN HIGHER SKILL LEARNING - Adenan Ayob; Lajiman Janoory, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Commonly, the main problem of technological in translation is to find out the importance and indeed the very nature of terminology that poorly understood by some students in higher skill learning institutions. Thus many people simply have no idea at all of what it is, while others, searching for an explanation of some sort, and end up associating it with different meaning. Related professions in the field of communications such as translation and technical knowledge will often be aware of the word without having precise of what it entails. This research highlights the benefits and challenges of Malay technological terminologies in higher skill learning institutions. Other than discussing the meaning of terminology and technology and their concept, this research recommends the proposed of methodology through content analysis that based on Catford Theory. This theory has made huge coverage of scientific research for technological terminologies. The results of this study showed that the benefits and challenges accelerate the collection process and creation critical knowledge. It is decide that the technological terminologies have to be developed in order to create technical skill of knowledge.